The Main Determinants of Inflation in South Africa: an Empirical Investigation - Madito, Oatlhotse; Odhiambo, Nicholas M. (Organizations and Markets in Emerging Economies, 2018)
This study investigated the determinants of inflation in South Africa using quarterly data from 1970Q1 to 2015Q4. The study was motivated by recent trends in domestic inflation that has frequently been at the upper end of the target range of between 3% and 6%, and the need to guide inflation-related policy since 2008. These recent trends raised concerns regarding the effectiveness of the current monetary policy approach in responding to internal and external factors that are significant in determining domestic inflation. Using Error Correction Model (ECM) modelling techniques, empirical results revealed that inflation expectations, labour costs, government expenditure and import prices are positive determinants, while GDP and exchange rates are negative determinants of inflation. To achieve the macroeconomic policy objective of a stable and low inflation rate for South Africa, more emphasis should be placed on anchoring inflation expectations, which was found to be highly significant in determining inflation.